The analysis of english loan word used in politics and business articles as found in tribun bali newspaper - Ni Kadek Martini; Komang Dian Puspita Candra; Putu Devi Maharani (Journal of Language and Applied Linguistics, 2022)
This study aims to find out the kinds of English loan word and their adaption process from English into Indonesian. The data were analyzed by applying the theory proposed by Hockett (1958) to find out the kinds of English loan word, and supporting theory from Haugen (1972) to find out the kind of adaption process. This study uses observation method in collecting the data and descriptive qualitative method in analyzing the data. This study concludes that there were 76 English loan word found in Tribun Bali Newspaper, those are 3 loanword, 61 loan shift, and 12 loan blend. For the adaptation process, there were morphological and phonological adaptation. For loanword, there is no changes in morphological and phonological adaptation. Furthermore, for loan blend and loan shift, morphological adaptation was found in the form of spelling and affixation of the words, meanwhile the phonological adaptation was found in term of pronunciation.